(3GdOhGFQ GdeJMQcI ef PGJgGs - (3CMeO Hf eMeO Hf YHO GdQMje Hf Gdhdjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI EPG CQOfG Cf fYed OGFQI JOhQ ef PGJgG aJUYO GdeGA hJOjQ QMG , aEfG fLO OGFQI ef GUdH eG jchf ef GdNTH s
(3BNQgG (B:s
(3ef BNQ GdehOhO hGdHcQI GdeSehQg aj GdGQV GdPj jOhQ YdjgG GdLHd Gdedaha Ydi GdecfI hGdecfI GdJj jOhQ YdjgG s
(3Vef eLehY , JQJjHgG (B: 2s
(3GNP ef cJGH adjf aj GdMjd GdQhMGfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GgOGAGJ O (B/ (3TRcjf ddeYgO s
Keywords: (3eJaQbGJs